2020
DOI: 10.21873/anticanres.14694
|View full text |Cite
|
Sign up to set email alerts
|

AMIGO2 Expression as a Potential Prognostic Biomarker for Gastric Cancer

Abstract: Background/Aim: Although our understanding of the molecular mechanisms of gastric cancer (GC) development and progression is steadily deepening, the clinical outcome of GC patients remains inadequate. The identification of molecules associated with GC will help improve prognosis. We aimed to identify the molecules involved in GC progression and metastasis. Materials and Methods: Transcriptome analysis was performed on surgically resected gastric tissue from patients with hepatic metastasis. Fourteen cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 29 publications
1
17
0
1
Order By: Relevance
“…The association between organ carcinogenesis and AMIGO2 expression has been reported in various types of cancer, including gastric cancer [ 13 , 14 ], pancreatic cancer [ 20 ], colorectal cancer [ 11 , 19 ], breast cancer [ 12 ], ovarian cancer [ 17 ], endometrial cancer [ 21 ], melanoma [ 15 , 16 , 40 ], and pituitary neuroendocrine tumors [ 18 ]. Since AMIGO2 expression is involved not only in tumor development but also in tumor progression including acquisition of metastasis, AMIGO2 may be a new molecule that controls cancer stem cell-like function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between organ carcinogenesis and AMIGO2 expression has been reported in various types of cancer, including gastric cancer [ 13 , 14 ], pancreatic cancer [ 20 ], colorectal cancer [ 11 , 19 ], breast cancer [ 12 ], ovarian cancer [ 17 ], endometrial cancer [ 21 ], melanoma [ 15 , 16 , 40 ], and pituitary neuroendocrine tumors [ 18 ]. Since AMIGO2 expression is involved not only in tumor development but also in tumor progression including acquisition of metastasis, AMIGO2 may be a new molecule that controls cancer stem cell-like function.…”
Section: Discussionmentioning
confidence: 99%
“…Multivariate analysis showed that AMIGO2 expression in patients with CRC was an independent predictive factor for liver metastasis [ 11 ]. Furthermore, transcriptionally high levels of AMIGO2 are associated with shortened survival of patients with CRC [ 11 ], breast cancer [ 12 ], and gastric cancer [ 13 ]. AMIGO2 has been reported as a novel pathogenesis-related gene in gastric cancer [ 14 ], melanoma [ 15 , 16 ], ovarian cancer [ 17 ], and pituitary neuroendocrine tumors [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, our histopathological study revealed a close association between AMIGO2 expression in primary tumors from patients with colorectal cancer and liver metastasis 6 . In addition, high AMIGO2 mRNA has been reported to be positively associated with disease-free survival and reduced overall survival in patients with gastric cancer 7 . Thus, AMIGO2 expression in cancer cells may enhance the adhesion of cancer cells to liver endothelial cells, thereby facilitating the formation of liver metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In ovarian cancer, cancer cells with high AMIGO2 expression show a significantly increased growth rate in the abdominal cavity [ 16 ]. In GC, patients with high AMIGO2 mRNA expression have a significantly worse prognosis [ 17 ].…”
Section: Introductionmentioning
confidence: 99%